PENGARUH PEMBERIAN REWARD TERHADAP MOTIVASI BELAJAR MATEMATIKA SISWA SMP - Rizqadariansyah Rizqadariansyah (Jurnal Education, 2025)
Learning motivation is one of the important factors that influence students' learning outcomes. Therefore, it is essential for teachers to pay attention to students' learning motivation by implementing engaging and enjoyable teaching methods. This study aims to determine the effect of reward provision on students' mathematics learning motivation. The method used in this research is classroom action research, with data collection techniques including observation, documentation, and tests. Data analysis is conducted using a descriptive approach. The sample in this study consists of students from class VIII-1 at SMP Negeri 30 Makassar. The results indicate that the provision of rewards positively affects students' mathematics learning motivation.